2020
DOI: 10.1002/mus.26788
|View full text |Cite
|
Sign up to set email alerts
|

Medial femoral cutaneous nerve conduction study with distal recording: A novel technique

Abstract: Background A new technique to obtain the sensory nerve action potential (SNAP) of the medial femoral cutaneous nerve is described. Methods SNAPs were recorded from 104 subjects with a bar recording electrode 10 cm proximal to the patella along an imaginary line drawn between the medial edge of the patella and the femoral pulse below the inguinal ligament. Stimulation was applied 14 cm proximal to the recording point. Results There were 104 healthy subjects. Onset latency of the SNAPs was 2.20 ± 0.16 ms (mean ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Despite no increase in neurological function, IFC was found significantly enhanced muscle function in our study. It is said that IFC induces involuntary contraction of skeletal muscle to promote its anabolism to increase fibronectin content in muscle and maintain or improve skeletal muscle mass and strength [ 46 , 65 70 ]. An in-depth study found that it may reduce the concentration of calcium in mitochondria and calcium overload by increasing the activity of Na + -K + -ATPase and Ca 2+ -Mg 2+ -ATPase, thus stimulates oxidative phosphorylation, which plays a central role in reducing fatigue and improving muscle function [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite no increase in neurological function, IFC was found significantly enhanced muscle function in our study. It is said that IFC induces involuntary contraction of skeletal muscle to promote its anabolism to increase fibronectin content in muscle and maintain or improve skeletal muscle mass and strength [ 46 , 65 70 ]. An in-depth study found that it may reduce the concentration of calcium in mitochondria and calcium overload by increasing the activity of Na + -K + -ATPase and Ca 2+ -Mg 2+ -ATPase, thus stimulates oxidative phosphorylation, which plays a central role in reducing fatigue and improving muscle function [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“… 18 Studies have shown that 2–30 Hz low frequency electrical stimulation may improve the hypoxia tolerance, treadmill fatigue, and swimming exhaustion times in mice; while 10–100 Hz low-frequency electrical stimulation can increase the fibrin content in the gastrocnemius muscle and promote the synthesis of skeletal muscle. 19 , 20 In our study, a combination of the low-frequency modulated medium frequency electrical stimulation (medium frequency, 2000–4000 Hz and low frequency, 1–167 Hz) was used. This frequency does not stimulate the skin sensory nerve endings and does not cause pain, which makes it ideal to ensure patient tolerance.…”
Section: Discussionmentioning
confidence: 99%